Communicating change in organizational restructuring: A grounded theory case study - Kamarudin, Mohd Fauzi; Starr, Karen; Abdullah, Aida Nasirah; Husain, Kalthom (Elsevier Ltd., 2014)
Literature has shown that planned change is accompanied by excitement and hope.People affected by change require quality information.Failure to communicate change may lead to resistance.This paper presents a change involving the amalgamation of two university faculties into one.Within the framework of a case study research design and the used of the Constructivist Grounded Theory for data collection and analysis, the theme of communication during the change process is presented through the experiences and life accounts of faculty members involved and affected by it.The paper ends with useful suggestions for change agents in today's complex organization.